군용항공기 생산공정에서 발생하는 예하중에 의한 주익 루트 페어링 지지대 균열개선 연구 - 신재혁(Jae Hyuk Shin); 정수헌(Su-Heon Jeong); 강구헌(Gu-Heon Kang); 이헌섭(Heon Sub Lee) (항공우주시스템공학회지, 2018)
Military aircraft may have fatigue cracks in structurally weak areas due to multiple factors such as the accumulation of flight time while perform various missions and unpredictable air conditions. As a fatigue crack progresses, there is a risk that the structure will be destroyed in extreme cases, which can have a significant impact on flight safety. In this study, a cracking phenomenon was observed during the periodic inspection the inner support of the fairing, which is installed to protect the connection between the wing and the body of the aircraft. Therefore, a study on a series of quality improvement processes for reformation was described. In order to identify the causes of cracks, pre-load generation occurrence during the wing assembly process was investigated and a fracture analysis was performed. Also, the design of the support structure was suggested in terms of preventing recurrence of cracks. The structural integrity was verified using a stress and fatigue life analysis. 군용항공기는 다양한 임무의 수행을 통한 비행시간 누적과 예상 불가능한 외기 환경에 의한 복합적인 요인으로 구조적으로 취약한 부위에서 피로균열이 발생할 수 있다. 피로 균열은 점차 진전되어 극심한 경우 해당 구조가 파괴될 위험이 있으며 이는 비행 안전성에 큰 영향을 미칠 수 있다. 본 논문에서는 항공기 주익과 동체의 연결부위를 보호하기 위해 장착한 페어링 내부의 지지대에서 주기검사 중 균열 현상을 개선하기 위한 일련의 품질개선에 관한 연구를 수행하였다. 균열의 원인파악을 위해 주익 조립 공정에 따른 예하중 발생 여부에 대해 조사하고 파단면 분석을 수행하였다. 또한, 균열의 재발방지를 위해 지지대의 설계를 개선하는 방안을 제시하였고, 응력 및 피로 수명해석을 통해 구조 건전성을 검증하였다.